Development of an Enrichment Book on the Dynamics of Life in River Watersheds from an Islamic Prophetic Paradigm Perspective - Devi Wulantika Nur Fitria; Azni Fajrilia (Future Space: Studies in Geo-Education, 2024)
The decline in watershed quality requires a handling role from the community. As part of society, students need to broaden their horizons, starting by studying watershed dynamics so they can carry out actual practice. Using the Islamic Prophetic Paradigm as a new perspective in learning can increase students' interest in general knowledge, religious fields, and practical examples of natural movements in everyday life. This research aims to develop an enriching book on the dynamics of river-watershed life from an Islamic prophetic paradigm perspective, intending to enhance students' learning and deepen their understanding of watershed dynamics by integrating scientific insights with Islamic teachings. The research and development of the ADDIE model uses questionnaire techniques in the form of pre-research questionnaires and validator questionnaires. The product's validity and feasibility level are tested using validity tests and field trials. The research data analysis technique uses descriptive qualitative analysis techniques and descriptive statistics. The research results show that the product follows learning outcomes, can increase students' interest in studying the Quran, and makes studying watershed dynamics easier. This research shows that product development is better than previous research and development. So, students can take advantage of this product.